2014
DOI: 10.1590/s1806-37132014000100003
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to the incorrect use of inhalers by asthma patients

Abstract: OBJECTIVE:To evaluate inhaler technique in outpatients with asthma and to determine associations between the correctness of that technique and the level of asthma control.METHODS:This was a cross-sectional study involving patients > 14 years of age with physician-diagnosed asthma. The patients were recruited from the Asthma Outpatient Clinic of the Hospital de Clínicas de Porto Alegre, in the city of Porto Alegre, Brazil. The patients completed two questionnaires (a general questionnaire and an asthma control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 12 publications
5
29
1
7
Order By: Relevance
“…This finding is consistent with those of the present study, because that was the second most common error made by our patients. Dalcin et al 24 found that the patients who used MDIs made more errors than did those who used other types of inhalers, a finding that is also consistent with those of the present study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This finding is consistent with those of the present study, because that was the second most common error made by our patients. Dalcin et al 24 found that the patients who used MDIs made more errors than did those who used other types of inhalers, a finding that is also consistent with those of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings corroborate those of other studies. 9 23 24 The inability to hold their breath for more than 10 s after inhalation was the major difficulty that our patients encountered during MDI and DPI use (83% and 75%, respectively). Manzella et al 12 assessed inhaler technique and reported that 69% of the patients studied did not hold their breath for at least 10 s. A review compiling the results of 12 studies (including 955 patients) identified the most common errors made by patients using inhaler devices, less than 10 s of breath-holding after inhalation having been observed in 26%.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In Jordan, one study showed that 71% of asthmatic patients poorly controlled . One prominent reason of poor asthma control is the poor inhaler technique, since by performing incorrect inhaler technique substantial reduction in lung deposition of the drug, and as consequence reduction in the effectiveness of the treatment and control . In our study, there is significant improvement in the level of control after education ( P = 0.000).…”
Section: Discussionsupporting
confidence: 47%
“…[1][2][3] A faulty inhaler technique incapacitates the patient from delivering adequate amount of medications to airways, leading to a low drug dose Improper inhaler technique has been attributed to various factors including age of the patient, education status, socioeconomic class, quality of training imparted, type of device used etc. [4][5][6][7][8] Presence of comorbidities including obesity, heart disease, cognitive impairment or neuropathy etc. also were found to be associated with improper inhaler use.…”
Section: Introductionmentioning
confidence: 99%